Dropwise condensation of acetone and ethanol for a high-performance lubricant-impregnated thermosyphon - Seo, Donghyun; Shim, Jaehwan; Shin, Dong Hwan; Nam, Youngsuk; Lee, Jungho (International Journal of Heat and Mass Transfer, 2021)
A gravity-assisted heat pipe called a two-phase closed thermosyphon (TPCT) is an efficient thermal device that transfers a large amount of heat at a relatively small temperature difference using the phase-change process. Promoting dropwise condensation on a condenser wall of a TPCT promises an increase in the effective thermal conductance of that device. Acetone and ethanol have been widely used for heat pipe applications as working fluids. Still, they pose a limitation in promoting dropwise condensation using typical hydrophobic coatings due to their lower surface energies. Recent works have shown that lubricant-impregnated surfaces (LIS) can promote dropwise condensation of low-surface-tension fluids, but no studies proved the effectiveness of the surfaces in TPCT applications. This study experimentally achieves dropwise condensation of acetone and ethanol within a TPCT using the LIS surface. We demonstrate heat transfer enhancement of a TPCT by examining temperature uniformity, condenser and evaporator heat transfer coefficients (HTCs), and overall and partial thermal resistances. We demonstrated that the LIS condenser increased the condenser HTC by 220% and decreased the overall thermal resistance of the TPCT by 44% compared to filmwise condensation. Our work also revealed a strong dependence of working fluid viscosity on dropwise condensation stability and heat transfer enhancement by comparing the two working fluids, acetone, and ethanol. This work presents the opportunity for improving thermal performance in heat pipes and applications that rely on the condensation of low-surface-tension fluids, such as HVAC, refrigeration, and organic Rankine cycle.
Keywords: Condensation of acetones; Dropwise condensation; Heat Transfer enhancement; Heat-transfer coefficients; Low-surface-tension; Lubricant-impregnated surfaces; SLIPS; Thermosiphon; Two-phase closed thermosyphon; Working fluid; Condensation; Heat pipe; Heat transfer; LIS; Low-surface-tension; SLIPS; Thermosyphon